Pengelolaan Penerimaan Peserta Didik Baru Di Sekolah Dasar - Nur Fadylla Istiqamah; Sumarlin Mus; Irmawati Irmawati (Universitas Negeri Makassar, 2023)
This study examines the management description of new student admissions at SD Negeri Sipala 1 Makassar. This study aims to determine the management, planning, and implementation of PPDB at SD Negeri Sipala 1 Makassar. The location of this research is centered in SD Negeri Sipala 1 Makassar. The study uses a qualitative approach with phenomenological research—data collection techniques using interviews, observation, and documentation. Data analysis uses data reduction, exposure, and conclusion drawing. I checked the validity of the data using triangulation techniques. The study results indicate that school management has been implemented and planned: (i) Planning is implemented by determining the capacity of prospective students; determining the conditions for the acceptance of prospective new students; preparation of PPDB information media; administrative preparation; and infrastructure. (ii) The implementation begins with the formation of the PPDB New Student Admission committee, which is formalized by using the Principal's Decree; making, sending/installing announcements; requirements for registration of new students, how to register, time of registration, place of registration, when is the result of registration; registration of prospective new students by taking the registration form at the school; determination of students who are accepted at the educational level